PENERAPAN SANKSI PIDANA TERHADAP ANAK DI BAWAH UMUR PENGEMUDI KENDARAAN BERMOTOR YANG MENYEBABKAN KEMATIAN - Mardatila M; Rahman Syamsuddin (Alauddin Law Development Journal)
This paper aims to determine the level of violations of motorized motorists in Gowa Regency from time to time. Not only those who can afford the law but also children. This is caused by the habit of parents who let their children drive motorized vehicles without having a license. The author is encouraged to conduct research on criminal sanctions that are appropriate for children as drivers of motor vehicles that cause death. The research method used is a type of normative research that is using literature studies and interviews to obtain data. Based on the provisions of Article 7 of Law Number 11 Year 2012 the author can conclude that the right of sanction to be applied to a child as a rider who causes someone's death is to use a transfer.